PENGEMBANGAN KOMIK DIGITAL BERBASIS KKEARIFAN LOKAL ENTANG CERITA RAKYAT CALON ARANG UNTUK SISWA KELAS V SDN SUKORAME 2 KOTA KEDIRI - Meliana, Eza; Wahid Ibnu Zaman; Zainal Afandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the results of the researcher's observations, that Indonesian language learning at SDN Sukorame 2 is still based on minimal use of learning media in the process of teaching and learning activities. As a result, the class atmosphere is boring, passive and monotonous. The objectives of this research are (1) to determine the validity of digital comic media for class V students (2) to determine the effectiveness of the validity of digital comic media for class V students (3) to determine the practicality of digital comic media for class V students. This research uses R&D research and development methods using the ADDIE model. The instruments of this research are observation and interviews. The conclusions of this research are (1) The results of media expert validation obtained a score of 92%, the results of material expert validation obtained a score of 96%. The average percentage score obtained from media and material experts is 94%, with very valid criteria. (2) The results of the teacher response questionnaire obtained a score of 94%, while the results of the student response questionnaire obtained a score of 92%. The average percentage score obtained from the teacher and student response questionnaire was 93%, with very practical criteria. (3) The results of the posttest score obtained a score of 91.60%, with a classical learning completeness of 93%, which is included in the very effective criteria.